Implementation of Criminal Sanctions Against Criminals of Humiliation and Defamation Through the Internet - Devi Ramadhona (Publikasi Indonesia, 2021)
Technological developments have made cybercrime rates continue to grow. One exampleis humiliation and defamation through the internet. The purpose of this study is to identify and analyze the factors that cause perpetrators to commit criminal acts of defamation through social media, the application of criminal sanctions against perpetrators of criminal acts of defamation through the internet in terms of the perspective of criminal law in Indonesia. Indonesia and identify and analyze efforts to overcome the occurrence of criminal acts of Information and Electronic Transactions (ITE). The approach taken in this research is normative and empirical juridical with data sourced from library research and field research. The results of this study indicate that the factors that cause perpetrators to commit criminal acts of defamation through social media are economic factors, socio-cultural factors, injury factors, and lack of legal awareness. Efforts to overcome the occurrence of criminal acts of Information and Electronic Transactions (ITE) are by